THE INFLUENCE OF SAFETY AND HEALTH, AND OFFICE FACILITIES ON EMPLOYEE PERFORMANCE (CASE STUDY OF PT MEARES SOPUTAN MINING) - Dumondor, Rosalia V. N (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The safety and health of the employees are really prioritized in every company. It will improve employee performance and provide benefits to the company for the smooth production process. Office facilities are the most important thing because employees need good and complete facilities to facilitate their activity in achieving the company goals. Office facilities can influence the employee performance because each employee has different abilities and work skill. Employee need help and complete facilities to do some works so they will perform better and increase their skills. The purpose of this research is to know the significant effect of Safety and health and office facilities on employee performance at PT Meares Soputan Mining. The type of this research is quantitative method by using multiple linear regression analysis. Type of data used is primary data by spreading the questionnaires to the employees where the sample size taken as much as 100 respondents. The result showed that Safety and health and office facilities have a significant affect on employee performance simultaneously. It also shows that Safety and health has a significant effect on employee performance partially and followed also office facilities has a significant effect on Employee Performance partially.Â Keywords: safety and health, office facilities, employee performance, multiple linear regressions